ANALISIS PRODUKTIVITAS TENAGA KERJA INDUSTRI KECIL KONVEKSI KABUPATEN TASIKMALAYA - Haaq, Moh Ihzarull; Sukarniati, Lestari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research aims to analyze and find out what factors influence the productivity of small convection industry workers in Tasikmalaya Regency, West Java. The variables observed in this research are length of work, education, training, gender and number of family dependents. In this research, the data source used is primary data, data was obtained by distributing questionnaires to forty-five respondents working in small convection industries in Tasikmalaya Regency. The type of data used is quantitative descriptive, analyzed using multiple linear models using the Eviews 12 analysis tool. The results of this research show that the variables of length of work, education, training and gender have a positive and significant effect on labor productivity, and the variable number of dependents does not has a positive and significant effect on labor productivity.